IMPROVING THE METHODOLOGY OF CREATING INNOVATIVE ELECTRONIC TEXTBOOKS IN THE SCIENCE OF GEOGRAPHY (American Journal of Interdisciplinary Research and Development, 2023)
In the article, the organization of the educational processes of general education schools based on modern approaches in the world educational practice, the problems of using electronic information educational resources in the teaching of geography in general education schools and their solutions, the creation of innovative electronic textbooks on geography and the importance of the effectiveness of education is discussed. Also, there are recommendations on the methodology of creating and using electronic information educational resources in geography education.